Synthesis and electrochemistry of octapentylthio phthalocyanine complexes of manganese, titanium and vanadium - Mbambisa, Gcineka (Rhodes University, Faculty of Science, Department of Chemistry, 2009)
Synthesis of new thio derivatised Pcs with manganese, titanium and vanadium as a central metal is reported. The complexes synthesised were characterised using spectroscopic and electrochemical means. The complexes displayed interesting spectroscopic properties with absorption of the Q band being observed in the near infrared region. These complexes have unusual colours for MPc complexes, with purple or red colour being observed in solution. Interesting electrochemical properties were observed, with rare observation of the MnIV/MnIII redox couple. There was observation of oxidation peaks for the pentylthio derivatised Pc with titanium as the central metal; this is unusual since for reported thio derivatives based on TiPc, no oxidation was observed. The vanadium based Pc showed an interesting spectrum for the first ring based reduction. The absorption spectrum obtained for the 1st reduction of the vanadium complex using spectroelectrochemistry would normally indicate a metal based process but comparing with literature it was concluded that it is a ring based reduction process. Generally all the MPc complexes formed a well ordered stable monolayer on the gold electrode. Electrocatalytic studies using L-cysteine revealed that the SAM based on manganese (III) octapentylthio phthalocyanine (AcOMnOPTPc) was the most effective since it catalyses L-cysteine at much lower oxidation potentials and it is also much more stable.
Keywords: Electrochemistry; Phthalocyanines -- Synthesis; Manganese; Titanium; Vanadium